Risk Stratification for the Intensive Care Unit Following Pancreaticoduodenectomy - Deichmann, Steffen; Ballies, Uwe; Petrova, Ekaterina; Bolm, Louisa; Honselmann, Kim; Frohneberg, Laura; Keck, Tobias; Wellner, Ulrich Friedrich; Bausch, Dirk (Zentralblatt für Chirurgie - Zeitschrift für Allgemeine, Viszeral-, Thorax- und Gefäßchirurgie, 2020)
Introduction In view of the limited capacities in intensive care units and the increasing economic burden, identification of risk factors could allow better and more efficient planning. Therefore, the aim of this study was to assess independent risk factors for the duration of intensive care unit stay after pancreatoduodenectomy (PD).Methods 147 patients who underwent pancreatoduodenectomy in the time period from 2013 to 2015 were identified from a prospective database and a retrospective analysis was performed. The primary endpoint was length of time spent in the ICU. A retrograde analysis was performed using univariate and multivariate regression analysis. All pre-, intra- and postoperative parameters were considered in the analysis.Results The median time spent in the intensive care unit (ICU) is one day. The univariate analysis demonstrated increased pack years, cerebrovascular events, anticoagulation, elevated creatinine and CA 19-9 as preoperative risk factors. In multivariate analysis, antihypertensive medication (AHT; OR 2.46; 95% CI 1.57 – 3.87; p = 0.05), operation time (OR 1.01; 95% CI 1.00 – 1.01; p = 0.03), extended LAD (OR 5.46; 95% CI 2.77 – 10.75; p = 0.01) and severe PPH (OR 4.01; 95% CI 2.07 – 7.76; p = 0.04) are significant risk factors for longer ICU stay.Discussion Patients with cardiovascular risk factors and elevated preoperative creatinine level are at greater risk for a prolonged ICU stay. Risk and benefit of an extended LAD should be weighed during the operation. Median duration on ICU/IMC after PD is one day or less for patients without risk factors. Whether routine monitoring in the ICU/IMC after PD is necessary must be clarified in further studies.
Keywords: pancreatic surgery; intensive medicine; abdominal surgery